Analysis of sulfur compounds using a water stationary phase in gas chromatography with flame photometric detection. Issue 7 (7th February 2017) - McKelvie, Kaylan H.; Thurbide, Kevin B.
Abstract : The properties of using a water stationary phase for analyzing organic sulfur compounds in capillary gas chromatography (GC) with a flame photometric detector (FPD) are presented. Abstract : The properties of using a water stationary phase for analyzing organic sulfur compounds in capillary gas chromatography (GC) with a flame photometric detector (FPD) are presented. The water phase was found to not hinder FPD performance, which provided a detection limit near 30 pg S s −1 and a selectivity of 3 × 10 4 for sulfur over carbon that agrees well with most commercial devices. Several different organosulfur compounds were examined and found to be retained to varying degrees on the phase. In many cases, analyte water solubility and polarity appeared to correlate well with retention, whereas analyte boiling point did not. By comparison, non-polar hydrocarbons were generally unretained in the system. This prevented their co-elution with sulfur analytes and the response quenching that is often observed in conventional GC-FPD. Of note, when a gasoline sample was analyzed on a standard DB-1 column, the response of the sulfur analytes present was found to be quenched by about 50% due to the overlapping hydrocarbon species also present. However, the same sample analyzed on the water stationary phase displayed no response quenching. Additionally, it was found that sulfur compounds present in different aqueous matrices such as wine, milk, and urine could also be readily and directly analyzed without interference, since many of the large hydrophilic matrix components present are often fully retained on the phase. Results indicate that this method can provide a useful alternative for the analysis of organosulfur compounds in complex matrices.